Preliminary Study on Mass Flow Rate in Passive Cooling Experimental Simulation During Transient Using NC-Queen Apparatus - M. Juarsa; J.H. Purba; H.M. Kusuma; T. Setiadipura; S. Widodo (Atom Indonesia, 2014)
The research related to thermal management has been significantly inreased, especially for NPP safety. The use of passive cooling systems both during the accident and operation become reliable in the advanced reactor safety systems. Therefore it should be enhanced through experimental studies to investigate heat transfer phenomenon of the heat decay in transient cooling condition.An investigation has been performed through experiment using an NC-Queen apparatusconstructed with rectangular loop. Piping were consisting of tubes of SS316L with diameter, length, and width of 3/4 inch, 2.7 m, and 0.5 m respectively. The height between heater and cooler was 1.4 m. The experiment used initial water temperature  at 70oC, 80oC, and 90oC in heater area. Transient temperature was used as experimental data to calculate water mass flow rate. The results showed that the temperature in heater area and cooler area were decreasing of about 90.6% and 95.7% at initial temperatur of 80oC, and of about 71.1% and 59.4% at initial temperature of 70oC. Those results were at higher initial temperature of 90oC compared with the initial temperature of 90oC. The average of water mass flow rate increased 81.03% from initial temperatur of 70oC. It was shown that the averages of removed heat in every second from water due to heat loss and cooler,were 3.51 watts, 5.06 watts and 6.85 watts respectively. The initial condition of heat stored in the water was quite different, but to the cooler heat removal capacity and heat loss was almost the same.Received: 10 November 2014; Revised: 23 December 2014: 24 December 2014